Approaches to Easy-To-Read Discourses: a case study - Gunta Rozina; Indra Karapetjana; Margarita Spirida (Baltic Journal of English Language, Literature and Culture, 2022)
In 2017, the organisation for Economic Cooperation and Development estimated that around 25 per cent of the population experiences difficulties in reading comprehension. The World Health Organisation (2021) has indicated that around 15 per cent of the world population faces functional impairment-related problems, which limit sufficient access to information unless the resources are adapted for meeting the needs of this layer of society. Considering the increasing numbers of the population who suffer from impairments at the language perception level, the present study has attempted to examine selected approaches that might serve for developing easy-to-read (EtR) discourses. Limited research has been conducted in the above-mentioned field, and the contributions that exist so far have focused on the linguistic and design features considered when producing EtR discourses; however, other central components that govern the adaptation of authentic texts for EtR needs seem to be neglected. Therefore, the present study aims to examine selected discourse-pragmatic approaches that can be applied for adapting texts to an EtR language. The present research is a qualitative case study targeted at EtR text developers and seeks to answer the research question: which discourse-pragmatic approaches should be considered to produce easy-to-read discourses? In conclusion, the paper offers the implications of the findings and reflects on the value of using discourse-pragmatic approaches to EtR discourse and cognitive load reduction.